On the Way to the Empire: the Portuguese Diplomacy of the Late Middle Ages - Diogo Faria (Studia Historica. Historia Medieval)
At the end of the Middle Ages, the kings of Portugal broadened their network of diplomatic contacts while several navigators, on their behalf, were exploring the Atlantic. In this work, based on empirical research on 15th-century embassies and ambassadors, the outlines of the Portuguese diplomacy of that time are presented, giving an account of who the interlocutors were, characterising the ways in which connections were established, addressing the importance of writing and the typology of the documents involved in the contacts, socially characterising the representatives of the monarchs and looking at the relevance of the ceremonies and rituals in these connections. It is intended, therefore, to point out what the external relations of the kings of Portugal of this period had in common with the diplomacy of the medieval West in general and to identify the specificities of the Portuguese case.